2013
DOI: 10.3329/bjmb.v6i1.13280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleurotus ostreatus on Blood Pressure and Glycemic Status of Hypertensive Diabetic Male Volunteers

Abstract: Different species of mushrooms are being used increasingly for their nutritional and medicinal values. They are used in traditional medical practice in the treatment and prevention of diabetes, obesity, heart diesaes, hyperacidity, cancer and hypertension. This study was designed to see the effects of Pleurotus ostreatus on blood pressure and glycemic status of hypertensive diabetic male volunteers. The study was carried out in the National Mushroom development and Extension Center (NAMDEC) laboratory, Savar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 13 publications
(10 reference statements)
0
44
0
Order By: Relevance
“…It was also observed that P. ostreatus decreased fasting plasma glucose levels and reduced the level of glycosylated haemoglobin. 86 The hypoglycaemic effect of freeze-dried and powdered P. ostreatus was also investigated with 22 healthy human volunteers and 28 type 2 diabetic patients on diet control at a dose of 50 mg per kg per body weight, followed by a glucose load. The P. ostreatus powder showed a significant reduction in fasting and the postprandial serum glucose levels of healthy volunteers and reduced the postprandial serum glucose levels and increased the serum insulin levels of type 2 diabetic patients.…”
Section: Hypoglycaemic Effectsmentioning
confidence: 99%
“…It was also observed that P. ostreatus decreased fasting plasma glucose levels and reduced the level of glycosylated haemoglobin. 86 The hypoglycaemic effect of freeze-dried and powdered P. ostreatus was also investigated with 22 healthy human volunteers and 28 type 2 diabetic patients on diet control at a dose of 50 mg per kg per body weight, followed by a glucose load. The P. ostreatus powder showed a significant reduction in fasting and the postprandial serum glucose levels of healthy volunteers and reduced the postprandial serum glucose levels and increased the serum insulin levels of type 2 diabetic patients.…”
Section: Hypoglycaemic Effectsmentioning
confidence: 99%
“…Daily doses of 3-5 g of P. ostreatus powder were found to decrease fasting plasma glucose level in both healthy people and type-2 diabetic patients (Agrawal et al, 2010;Choudhury et al, 2013). powder on both healthy and unhealthy humans.…”
mentioning
confidence: 99%
“…powder on both healthy and unhealthy humans. Daily doses of 3-5 g of P. ostreatus powder were found to decrease fasting plasma glucose level in both healthy people and type-2 diabetic patients (Agrawal et al, 2010;Choudhury et al, 2013). Slightly higher daily doses, in the range 5-10 g, were found to enhance the innate and acquired immune responses in healthy human subjects (Sun et al, 2014).…”
mentioning
confidence: 99%
“…Bobek Hossain et al [2003], Khatun et al [2007] pulverized mushrooms Choudhury et al [2013] Hypocholesterolemic lectin Devi et al [2013Devi et al [ ], (2015 Anti-inflammantory polysaccharides (1,3), (1,6)-linked ß-glucan Bobek and Galbavý [2001], Smiderle et al [2008], Jedinak et al [2011] Indole compounds. Higher fungi, including Pleurotus ostreatus are a good source of non-hallucinogenic indole compounds and their derivatives.…”
Section: Lovastin Ergothioneinementioning
confidence: 99%